Gated nature and its role in creating place attachment and place identity in post-apartheid South Africa: an analysis of Grotto Bay private residential estate - Ramsawmy, Sharon (Department of Environmental and Geographical Science, 2018)
This dissertation focuses on a private residential estate, known as Grotto Bay, situated on the West Coast of the Western Cape province of South Africa. It examines the motivations of its participants to move to a non-metropolitan gated community and focuses on the participants' experiences of life in gated nature. In analysing the participants' subjective experiences, this work aims to understand how such experiences contribute to the development of place attachment, against the backdrop of the understanding of whiteness in the post-apartheid landscape. This qualitative, ethnographic research uses semi-structured interviews and participant observation to collect data. To analyse the data collected, this research uses thematic content analysis of texts and observations to identify motivations and link them to the body of literature on gated communities and lifestyle migration in South Africa. Drawing on the Person, Place and Process Framework, this work further probes into an understanding of the processes of place attachment to Grotto Bay, by speaking back to insights from the literature on place attachment, landscape and identity, within the post-apartheid South African context. The findings show that through gating and a migration back to the rural land, the participants of this research have enlisted the natural landscape to root themselves to place and to find a sense of continuity in self and in their identity, by linking the reconstruction of their past with the present and future. The results further indicate that discourses of withdrawal and attachment to place, read through a lens of white privilege, drive the making and re-making of boundaries in the post-apartheid context of South Africa. This work shows that through the privatisation of the rural landscape, Grotto Bay facilitates notions of power and control through the respondents' romantic and nostalgic idealisation of their new social imaginary. The respondents' subjective experiences exemplify the ways in which estates such as Grotto Bay may stand to perpetuate white hegemony and environmental injustice in the post-colonial and post-apartheid contexts.